Gender mainstreaming in sweet potato breeding in Uganda - Ssali, Reuben T.; Mayanja, Sarah; Nakitto, Mariam; Mwende, Janet; Tinyiro, Samuel Edgar; Bayiyana, Irene; Okello, Julius; Forsythe, Lora; Magala, Damalie; Yada, Benard; Mwanga, Robert O.; Polar, Vivian (International Potato Center, 2023)
Purpose: In Uganda, sweet potato is typically a “women’s crop” grown by smallholder farmers for food and income. Farmers value sweet potato for its early maturity, resilience to stresses, and minimal input requirements. However, productivity remains low despite the effort of breeding programs to introduce new varieties. Low uptake of new varieties is partly attributed to previous focus by breeders on agronomic traits and much less on quality traits and the diverse preferences of men and women in sweet potato value chains. Method: To address this gap, breeders, food scientists, and social scientists (including gender specialists) systematically mainstreamed gender into the breeding program. This multidisciplinary approach, grounded in examining gender roles and their relationship with varietal and trait preferences, integrated important traits into product profiles. Results: Building on earlier efforts of participatory plant breeding and participatory varietal selection, new interventions revealed subtle but important gender differences in preferences. For instance, in a study for the RTBfoods project, women prioritized mealiness, sweetness, firmness and nonfibrous boiled roots. These were further subjected to a rigorous gender analysis using the G+ product profile query tool (Ashby and Polar, 2021; CGIAR 2021). The breeding pipelines then incorporated these gender-responsive priority quality traits, prompting the development of standard operating procedures to phenotype the PQTs. Conclusion: The product advancement and joint decision-making meetings have further positioned sweet potato breeding to better respond to the varying needs and preferences of the users